Pathogenic Assay of Leaf Blight Pathogen on Maesopsis eminii Engl. in Permanent Nursery BPDAS Bogor UJI PATOGENISITAS PATOGEN HAWAR DAUN PADA TANAMAN KAYU AFRIKA (Maesopsis eminii Engl.) DI PERSEMAIAN PERMANEN BPDAS BOGOR - Muhammad Alam Firmansyah; Muhammad Hario Alfarisi (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
Maesopsis eminii (Engl.) is a fast-growing tree species which are now begin to be exploited. This research was aimed to identify types of pathogens, disease incidence and severity of leaf blight disease in Maesopsis eminii seedlings. Methods include field observations, isolation of symptomatic leaf blight and subsequent testing of Koch's postulates. Results of field observations indicating that the incidence of the disease is at 99.44%, while the severity of the disease by 8.85%. When isolation of symptomaticleaf blight was found 8 kinds of isolate that have different colors. The isolates were found in plants are then inoculated on Maesopsis eminii, and almost all isolates can causing the symptoms of leaf blight. The result of Koch's postulates inoculated leaf, found two types of isolates were identical to the initial isolation. Pathogenicity test results showing isolates with 1.1 code has the highest percentage value of disease incidence and severity than the other isolates. The identification results show the isolates with 1.1 code is a type of fungus characterized by having sectional hyphae and contained conidia, this fungus belongs to a class of Deuteromycetes.Key words: Fungus, Koch's postulates, leaf blight, Maesopsis eminii Engl., severity of disease